High-resolution x-ray spectroscopy with superconducting tunnel junctions - Hettl, P; Angloher, G; Von Feilitzsch, F; Hohne, J; Jochum, J; Kraus, H; Mossbauer, R (1999)
An energy resolution of Delta E = 12 eV (FWHM) was measured for the Mn-55 K alpha(1) line (E = 5.90 keV) using a single superconducting Al/AlxOy/Al tunnel junction. The total detector area of 100 x 100 mu m was illuminated, while a slit mask of about 150 mu m width was used to shadow the detector leads and substrate area from the impinging x-rays. The total electronic noise contribution to the energy resolution was measured as Delta E-elec = 7 eV (FWHM). The process of tunnel junction fabrication was optimized towards a reproducible and high-quality growth of the tunnel barrier. High-quality aluminium films promote long quasi-particle lifetimes and ensure reproducible tunnel barrier growth. The residual resistance ratio of a 1 mu m thick aluminium test film was about 100, Copyright (C) 1999 John Wiley and Sons, Ltd.